The characteristics and perception of small wind system noise - Taylor, Jennifer (2012)
The UK has committed to sourcing 15% of its energy from renewable sources by 2020 and wind turbines have the potential to contribute towards this target. Due to the Feed-In-Tariffs introduced by the UK Government in 2010, the potential uptake of micro-generation methods such as small wind is likely to increase. However, many barriers exist which prevent widespread implementation, such as noise concerns. There is little work available in the open literature quantifying the problem because much of the existing research focuses on large scale turbines. The need for an increase in interdisciplinary research in this area has also been called for.